PUBLIC RELATION MANAGEMENT IN INCREASING PUBLIC CONFIDENCE IN MADRASAH - Huda, Unsil Al; Rahmatillah, Alda Novita; Abdullah, Abdullah; Sholihah, Imroatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the role of public relations management in increasing public trust in madrasahs. Public trust is an important element that influences the success of educational institutions, including madrasahs. In this context, public relations serves as a communication bridge between madrasahs and the community, aiming to build a positive image and increase public participation. This research uses a qualitative approach with a case study method in several madrasahs in Indonesia. The results of this study are expected to show that public trust in madrasah is influenced by the ability of public relations to build effective communication, information transparency, and program implementation that actively involves the community. The main strategies used by public relations include involving parents in school activities, publicizing academic and non-academic achievements, and strengthening the madrasah image through social media. Factors supporting success include support from the madrasah leadership, synergy between teachers and staff, and innovation in delivering information. In contrast, the challenges faced include limited human resources and technology. In addition, this study highlights the importance of training for the public relations team at madrasah Ibtidaiyah Bahrul Ulum Watupanjang Village, Krucil Sub-district, Probolinggo District to improve their communication skills. With proper training, the PR team can be more effective in delivering positive messages to the public. This is in line with the theory of public relations as a liaison that emphasizes the role of public relations in establishing good relations between the organization and the public. This study concludes that the optimal role of public relations contributes significantly to increasing public trust, so it needs to be supported by policies that support strengthening the capacity of public relations in madrasah.